Bases for the Dialectological Characterization of the Speech of the Municipality of Castrelo do Val and of Galician as a Whole, and its Relationship with Linguistic Change - Alonso Núñez, Aquilino Santiago (Madrygal. Revista de Estudios Gallegos, 2023)
This research explains the bases of the dialectological proposal for the municipality of Castrelo do Val, through the use of surveys and recordings as methods of investigation. It also aims at outlining a dialectological proposal of Galician as a whole taking into account long-term linguistic change. In the municipality of Castrelo do Val, where different speeches characterize each place, four linguistic convergences occurred as a result of history, geography and neighborhood. This could be extrapolated to the rest of Galician. In fact, it is argued that the variety of Galician without explosive seseo is the most common one (in other words, it occupies the largest area), which generally coincides with the Galician of the central block of Fernández Rei. However, the lack of a state of its own and of its centralizing apparatus has led to cases of linguistic convergences that only reach some areas of Galicia without constituting a true Galician koiné (aira), which differs from the standard variant. The Galician of the region of Verín converges in many cases with the Galician standard variety but also presents orientalizing features (cantais, tu, alustro, fraga, muito), which are also meridionalizing because they have continuity in the neighboring Portuguese.